Women in Coeducational Universities: A Study of the Women's Department at Cheeloo University - CHEN, Daitian (Journal of Research for Christianity in China (JRCC), 2025)
Cheeloo University was a Christian institution supported by ten missionary societies. It served as a pioneer not only in the history of Christian higher education in China but also in the history of women's higher education in China. As the first university in China to award bachelor's degrees to women, it differed from women's colleges by implementing coeducation as its foundational model, while simultaneously establishing an independent women's division to provide higher education for women. The mission of Cheeloo University's women's division was to cultivate female leaders for China and its Christian community. On campus, female missionaries with a strong sense of “feminine consciousness” actively advocated for the rights of female students. Off campus, the coeducational environment gradually narrowed gender gaps, enabling female graduates to assume positions traditionally held by men. The liberation of educational rights paved the way for the liberation of working rights, collectively advancing women's rights in modern Chinese society.
Keywords: Cheeloo University, Women's Education, Coeducation, Women's Rights, Modern Christian Women's Higher Education